An Addiction Detection Application Playing Free Fire Games Based on Android Using Tsukamoto's Fuzzy Logic: Aplikasi Pendeteksi Kecanduan Bermain Game Free Fire Berbasis Android Dengan Menggunakan Logika Fuzzy Tsukamoto - Hasan Basri; Mochamad Alfan Rosid (Academia Open, 2021)
Online games that have a battle royal genre nowadays are very much the inantantnya. One of them is Free Fire which has been downloaded by more than 100 million people. The high number indicates that a person's high interest in playing online games can have a negative impact on one of them. For that, there is an app that can detect how much fun a person has in playing Free Fire games. By utilizing the fuzzy logic method tsukamoto allows it to detect the level of addiction of a person which is an android-based application. By utilizing the data owned by each player as an input variable that will produce output in the form of an addiction level percentage. Utilization of fuzzy tsukamoto method is expected to provide the right conclusions and in accordance with the expected.